FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN KONSUMEN PADA SWALAYAN MIKRO DI KOTA SEMARANG - hendri hermawan adinugraha (MediaTrend, 2018)
ABSTRACT: There is a big number of modern market in Indonesia. Based on the data, market share of Superindo, Hero, Griya and Micro Supermaarket have declined. Nevertheless, MICRO market share has declined the smallest and the lowest ranking. Based on this phenomenon, indicated there are problems which feasible to be analyzed. The object of this research is Micro Supermaarket Semarang. Many factors can influence purchasing decisions in Micro Supermarket Semarang, such as location, physical evidence, store atmosphere and the variety of merchandise. This study aims to analyze the influence of location, physical evidence, store atmosphere and the variety of merchandise on purchasing decision. The data population is consumers who make purchases at the Micro Supermarket Semarang and the samples taken 100 respondents. The type of data used primary data. Sampling technique used non-random type of purposive sampling. The methods of data collection using questionnaires and analysis techniques used multiple regression. The results show that location, physical evidence, store atmosphere and the variety of merchandise proved a positive and significant influence on purchasing decision.